Amphiphobic PVDF composite membranes for anti-fouling direct contact membrane distillation - Lu, X.; Peng, Y.; Ge, L.; Lin, R.; Zhu, Z.; Liu, Shaomin (2016)
© 2015 Elsevier B.V. This study aimed to develop an effective method to fabricate the amphiphobic polyvinylidene fluoride (PVDF) composite membranes for membrane distillation (MD) with excellent tolerance to various organic foulants. A facial surface modification method was explored to obtain amphiphobic membranes with mechanical and thermal robustness by dynamically forming perfluorooctyl trichlorosilane (PFTS) and coating SiO2 nanoparticles onto the membrane surface. A variety of techniques such as environmental scanning electron microscopy (ESEM), Fourier transform infrared spectrometry (FTIR), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM), liquid entry pressure (LEP) measurement and contact angle goniometry were applied to examine the effects of surface modification on surface chemistry, morphology and wettability of the derived membranes. The surface modification conferred the modified membrane superhydrophobicity and oleophobicity, stemmed from micro-fluorinated SiO2 particles covering the membrane surface. The anti-fouling property of the pristine and modified membranes were examined in a direct contact membrane distillation (DCMD) process using sodium chloride solution containing three model foulants (hydrophobic, hydrophilic or amphiprotic). The dynamically formed SiO2-PFTS/PVDF-2 membranes exhibited good thermal and mechanical resistance for DCMD operation. DCMD test showed that the surface modification did not sacrifice the permeate flux and the salt rejection. By adding the organic foulants, the pristine membrane displayed severe permeate flux decay and salt penetration. In contrast, the modified membrane presented a stable permeate flux and high salt rejection with the presence of three foulants respectively. The anti-fouling and anti-wetting properties of the modified membrane could be attributed to the enhanced amphiphobicity of membrane surface.